Reconhecimento e consenso em Henrique Cláudio de Lima Vaz - Bartelli, Gerson (My University, 2021)
This dissertation aims to present the conceptual pair recognition and consensus in the philosophical ethics of Lima Vaz, as a possible way to overcome the Western ethical crisis, awakened from the program of modernity and ethical nihilism. Linked to these terms will be seen their correlated pair, equity and equality. In order to overcome individualism, the community will be presented as a principle and not as a result of the agglomeration of individuals. The subject, being-of-relationships, in the reciprocity of acts, in the ethical community forms the We, recognizing and consenting the presence of equality in the dignity of the Other. The community is presented as a space for the expression of ethical life, being fundamental for the development of the moral person, having justice as its fundamental principle. Justice, as virtue and law, will be responsible for responding to the split between Ethics and Right. This split resulted in a hypertrophy of the law as justice. The problem surrounding the objective of this work is the program of modernity and the overcoming of ethical nihilism, being necessary to establish a meaning for life, that is, to offer an ethical orientation for the subject's action. Therefore, it will be important to understand how the author understands the idea of ethos, as a symbolic set of rules and laws. The ethos is carried by tradition throughout the history of the communities, being formed by customs. The idea of Good is understood as the end of the action of the subject and the ethical community. This teleology is a link of unity among the members of the community, since everyone must direct their actions towards the Good, that is, towards the best, preserving the unity of the social fabric. Finally, through recognition and consensus there is the possibility, in the reciprocal relationship, of accepting the different that is equal in dignity, overcoming intolerance, disrespect and hatred towards the Other-Self in the ethical community. Undoubtedly a very current topic. [resumo fornecido pelo autor]
Esta dissertação tem por objetivo apresentar o par conceitual reconhecimento e consenso na ética filosófica de Lima Vaz, como possível caminho para a superação da crise ética ocidental, despertada a partir do programa da modernidade e do niilismo ético. Ligado a estes termos será visto o seu par correlato, equidade e igualdade. Para a superação do individualismo, a comunidade será apresentada como princípio e não como resultado da aglomeração dos indivíduos. O sujeito, ser-de-relações, na reciprocidade dos atos, na comunidade ética forma o Nós, reconhecendo e consentido a presença da igualdade em dignidade do Outro. A comunidade é apresentada como espaço de expressão da vida ética, sendo fundamental para o desenvolvimento da pessoa moral, tendo a justiça como seu princípio fundamental. A justiça, enquanto virtude e lei, será responsável por responder à cisão entre ética e direito. Esta cisão resultou numa hipertrofia da lei como justiça. A problemática em torno do objetivo deste trabalho é o programa da modernidade e a superação do niilismo ético, sendo necessário estabelecer um sentido para a vida, isto é, oferecer uma orientação ética para ação do sujeito. Diante disso será importante entender como o autor compreende a ideia de ethos, enquanto conjunto simbólico de normas e leis. O ethos é transportado pela tradição ao longo da história das comunidades, sendo formado pelos costumes. A ideia de Bem é compreendida como fim da ação do sujeito e da comunidade ética. Essa teleologia é elo de unidade entre os membros da comunidade, uma vez que todos devem direcionar suas ações para o Bem, isto é, para o melhor, preservando a unidade do tecido social. Por fim, pelo reconhecimento e consenso tem-se a possibilidade, na relação de reciprocidade, da aceitação do diferente que é igual em dignidade, superando a intolerância, o desrespeito e o ódio diante do Outro-Eu na comunidade ética. Sem dúvida um tema muito atual. [resumo fornecido pelo autor]
Keywords: Vaz, Henrique Cláudio de Lima, 1921-2002; Reconhecimento (Filosofia); Niilismo (Filosofia); Ética; Recognition (Philosophy); Nihilism (Philosophy); Ethic